Space charge lens for focusing negative ion beams - Goretsky, V.P.; Soloshenko, I.A.; Shchedrin, A.I. (Вопросы атомной науки и техники, 2000)
The idea of space charge lens for focusing negative ion beam is set forth. With the use of this lens focusing of H– ion beam with 10 keV energy and 30 mA current is realized. Focal length value of ~ 12 cm is reached.